2012
DOI: 10.1016/j.ddmec.2013.02.001
|View full text |Cite
|
Sign up to set email alerts
|

The etiology and prevention of breast cancer

Abstract: Metabolism of estrogens via the catechol estrogen pathway is characterized by a balanced set of activating and protective enzymes (homeostasis). Disruption of homeostasis, with excessive production of catechol estrogen quinones, can lead to reaction of these quinones with DNA to form depurinating estrogen-DNA adducts. Some of the mutations generated by these events can lead to initiation of breast cancer. A wealth of evidence, from studies of metabolism, mutagenicity, cell transformation and carcinogenicity, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 107 publications
0
12
0
Order By: Relevance
“…Several mechanisms have been postulated regarding the etiology and progression of breast cancer (2). Among these mechanisms, chronic inflammation is widely recognized to play a crucial role in cancer development, progression, and risk of recurrence due to its effects on carcinogenesis and the tumor microenvironment (3).…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms have been postulated regarding the etiology and progression of breast cancer (2). Among these mechanisms, chronic inflammation is widely recognized to play a crucial role in cancer development, progression, and risk of recurrence due to its effects on carcinogenesis and the tumor microenvironment (3).…”
Section: Introductionmentioning
confidence: 99%
“…Unbalanced estrogen metabolism is a critical factor in cancer initiation. The discovery that specific oxidative metabolites of estrogens, the catechol estrogen quinones, react with DNA supports the hypothesis that estrogens can become endogenous carcinogens by generating the mutations leading to the initiation of cancer [11–14]. This paradigm indicates that specific, critical mutations produce abnormal cell proliferation leading to cancer, rather than ER‐mediated abnormal cell proliferation that generates random mutations [1, 6–10].…”
Section: Mechanism Of Metabolic Activation Of Estrogens To Initiate Cmentioning
confidence: 99%
“…Over the last few years, several mechanisms have been postulated regarding the etiology and progression of breast cancer. 3 It has been shown that chronic inflammatory responses play essential roles in development of all kinds of cancers. Inflammatory cells can regulate the tumor microenvironment and are clearly implicated in tumor development by facilitating proliferation, migration, and survival.…”
Section: Introductionmentioning
confidence: 99%